Evaluation of the Relation between Noise and Vibration Exposure with Job Burnout in City Bus Drivers - Rahimimoghadam, Somayeh; Javan, Safoora; Nourmohammadi, Mohammad; Bayat, Sara; Harati, Zahra; Yari, Saeed; Kheyrkhah, Atefeh (Asian Pacific Journal of Environment and Cancer, 2023)
Introduction: Today, burnout has emerged as a significant concern affecting the well-being of employees within various groups and organizations. Numerous factors, including vibrations and noise, have been identified as impacting job burnout. City bus drivers are individuals who are frequently exposed to a wide range of stressors and pressures. Consequently, this study aims to evaluate the influence of noise and vibration exposure on job burnout specifically city bus drivers in Neyshabur. Material and method: In the conducted study, a total of 62 bus drivers from Neishabur city participated. To accurately measure sound levels, a TES dosimeter was employed, while vibration levels were assessed using an SV 106 vibration meter. As for job burnout, the researchers utilized the well-established Maslach questionnaire. Result: The present study reveals notable findings regarding the frequency levels of various dimensions among bus drivers. Particularly, the dimension of emotional exhaustion and depersonalization exhibited the highest percentage at a medium level. Moreover, all bus drivers scored high on the dimensions of lack of success and lack of efficiency. the dimension of emotional exhaustion and depersonalization was found to have the highest frequency percentage, particularly at a medium level. Results from the correlation test indicated a significant relationship between emotional fatigue and various factors, such as the number of working hours per week, amount of overtime per week, number of services, and exposure to vibrations. Additionally, a significant relationship was observed between the depersonalization dimension and the number of services, noise exposure, as well as lack of success and the number of services. Furthermore, a significant relationship between the lack of success dimension and the number of services and exposure to vibrations was identified. Conclusion: Factors such as the quantity of working hours, overtime, the number of services within the driving profession, as well as exposure to high levels of noise and vibration, have been identified as influential factors on job burnout. It is plausible to mitigate work burnout in driving occupations by implementing strategies such as reducing working hours, utilizing contemporary and low-vibration vehicles, and rotating work shifts between drivers in bustling and clamorous locales with more serene urban environments.